2016
DOI: 10.1158/0008-5472.can-15-2186
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation HSP90 Inhibitor Onalespib Blocks mRNA Splicing of Androgen Receptor Variant 7 in Prostate Cancer Cells

Abstract: Resistance to available hormone therapies in prostate cancer has been associated with alternative splicing of androgen receptor (AR), and specifically, the expression of truncated and constitutively active AR variant 7 (AR-V7). The transcriptional activity of steroid receptors, including AR, is dependent on interactions with the HSP90 chaperone machinery, but it is unclear if HSP90 modulates the activity or expression of AR variants. Here, we investigated the effects of HSP90 inhibition on AR-V7 in prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 52 publications
(79 reference statements)
0
72
0
1
Order By: Relevance
“…We also found that onalespib, another type HSP90 inhibitor [31], amplified the IL-6 release induced by PGF 2α in these cells. In addition, we showed that the expression levels of IL-6 mRNA induced by PGF 2α were markedly amplified by geldanamycin and onalespib.…”
Section: Discussionmentioning
confidence: 60%
“…We also found that onalespib, another type HSP90 inhibitor [31], amplified the IL-6 release induced by PGF 2α in these cells. In addition, we showed that the expression levels of IL-6 mRNA induced by PGF 2α were markedly amplified by geldanamycin and onalespib.…”
Section: Discussionmentioning
confidence: 60%
“…Instead, increased AR-V7 production is due to elevated AR pre-mRNA substrates for those splicing factors (Liu et al 2014b). Furthermore, the study of Ferraldeschi et al implicated a role for the molecular chaperone, HSP90, in AR-V7 splicing (Ferraldeschi, et al 2016). HSP90 inhibition leads to the disruption of AR-V7 splicing and reduction of AR-V7 level (Ferraldeschi et al 2016).…”
Section: Ar-v Productionmentioning
confidence: 99%
“…Furthermore, the study of Ferraldeschi et al implicated a role for the molecular chaperone, HSP90, in AR-V7 splicing (Ferraldeschi, et al 2016). HSP90 inhibition leads to the disruption of AR-V7 splicing and reduction of AR-V7 level (Ferraldeschi et al 2016). Finally, another study highlighted the interplay between the noncoding RNA PCGEM1 and splicing factors in contributing to AR splicing (Zhang, et al 2016).…”
Section: Ar-v Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of HSP90 with onalespib was also observed to alter AR splicing and lower the expression of AR-V7 [37]. Furthermore, Yamashita et al [38] were able to reduce CWR22Rv1 xenograft tumor growth by the addition of ASC-J9, a drug that degrades AR-V3 and full length AR.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%